Edukasi Shaken Baby Syndrome Sebagai Upaya Mencegah Perilaku Kekerasan Anak Di Masyarakat - Dessy Ekawati; Nurul Azmi; Titis Eka Setiyaningsih (FKIP, Universitas Palangka Raya, 2023)
Introduction: The background to this community service emerged due to increasing violence in the care of shaken babies, which can have a negative impact on child development. The aim of this service is to provide education to parents and caregivers about safe and caring care for babies, so that they can prevent incidents of shaken baby syndrome and cases of violence against children. Method: This Community Service uses a pre-post test design method to determine the level of knowledge of fathers before and after providing educational outreach on shaken baby syndrome (SBS). The population in this activity were fathers aged 18 – 30 years who had just had a child or had a second child within a year of the couple's postpartum period, numbering 150 people. The sample used in this activity was 60 people using a sampling technique, namely cluster area random sampling. Results: The results of this study showed that there was an increase in knowledge between before and after being provided with education about shaken baby syndrome (SBS), namely that 38 respondents (63.3%) had a sufficient level of knowledge about shaken baby syndrome (Shaken Baby Syndrome). SBS). Conclusion: Increasing knowledge about shaken baby syndrome is a key step in efforts to prevent violent behavior in children.